Durability of sustainable repair mortars exposed to industrial environments - Mendoza-Rangel, J. M.; Flores-Jarquín, J. M.; de los Santos, E. U.; Garcés Terradillos, P. (Revista ALCONPAT, 2016)
The repair and maintenance of concrete structures has increased in the activities of the construction industry. In this work, the durability of two mortars elaborated with fly ash substitutes (FA) is evaluated by weight with respect to the total cement; furthermore, its performance is compared to three commercial repair mortars, exposed to the CO2 attack in an industrial environment. To evaluate its performance as repair material, tests were carried out to evaluate its resistance to compression, bending, and adherence. Durability tests are also presented as potential measurements, corrosion rate, permeability, and carbonation depth. Keywords: mortar; repairing materials; corrosion; carbonation; durability.